Cercyon (Cercyon) alpinus Vogt, 1968 (Coleoptera: Hydrophilidae, Sphaeridiinae) – nowy dla fauny Polski gatunek chrząszcza - Czesław Greń; Lubecki, Krzysztof (Zenodo, 2021)
Cercyon ( Cercyon ) alpinus Vogt, 1968 (Coleoptera: Hydrophilidae, Sphaeridiinae) – new beetle species for the fauna of Poland. Cercyon alpinus Vogt, 1968 was collected in the Bieszczady Mts. This is the first record of this species from Poland. : {"references": ["Archangelsky M. 1999. Adaptations of immature stages of Sphaeridiinae (Staphyliniformia, Hydrophiloidea: Hydrophilidae) and state of knowledge of preimaginal Hydrophilidae. Coleopterists Bulletin 53: 64\u201379.", "Boukal D.S., Boukal M., Fik\u00e1\u010dek M., H\u00e1jek J., Kle\u010dka J., Skalick \u00fd S., \u0160\u0165asn\u00fd J., Tr\u00e1vn\u00ed\u010dek D. 2007. Catalogue of water beetles of the Czech Republic. Klapalekiana 43 (Suppl.): 1\u2013289.", "Burakowski B., Mroczkowski M., Stefa\u0144ska J. 1976. Chrz\u0105szcze \u2013 Coleoptera. Adephaga pr\u00f3cz Carabidae, Myxophaga, Polyphaga: Hydrophiloidea. Katalog Fauny Polski 23(4): 1\u2013307", "Fik\u00e1\u010dek M. 2006. Taxonomic status of Cercyon alpinus, C. exorabilis, C. strandi and C. tatricus and notes on their biology (Coleoptera: Hydrophilidae: Sphaeridiinae). Annalen des Naturhistorischen Museums in Wien 107 B: 145\u2013164.", "Fik\u00e1\u010dek M. 2019. Hydrophilidae Leach , 1815, In: Australian Beetles: Archostemata, Myxophaga, Adephaga, Polyphaga, \u015alipi\u0144ski, A., Lawrence, J. (Eds.), CSIRO Publishing: Clayton, CA, USA, Vol. 2: 271\u2013337.", "Fik\u00e1\u010dek M., Angus R.B., Gentili E., Jia F., Minoshima Y.N., Prokin A., Przewo\u017any M., Ryndevich S.K. 2015. Hydrophilidae, In: Catalogue of Palaearctic Coleoptera. Hydrophiloidea \u2013 Staphylinoidea. Revised and Updated Edition, L\u00f6bl I., L\u00f6bl D. (Eds.), Koninklijke Brill NV: Leiden- Boston, Vol. 2, pp. 37\u201376.", "Gre\u0144 C., G\u00f3rz A. 2020. Coprophagous hydrophilid beetles (Coleoptera, Hydrophilidae, Sphaeridiinae) distribution in the Polish Carpathians. Insects 11: 355. doi.10.3390/insects11060355, pp. 27", "Gre\u0144 C., Szo\u0142tys S., Grzywocz J., Kr\u00f3lik R. 2015. Chrz\u0105szcze (Coleoptera) \u015al\u0105ska Dolnego i G\u00f3rnego \u2013 dotychczasowy stan poznania oraz nowe dane faunistyczne: ka\u0142u\u017cnicowate (Hydrophilidae). Acta entomologica silesiana 23: 97\u2013120.", "Hansen M. 1987. The Hydrophiloidea (Coleoptera) of Fennoscandia and Denmark. Fauna Entomologica Scandinavica 18: 1\u2013254.", "Hansen M. 1991. The Hydrophilid beetles. phylogeny, classification and a revision of the genera (Coleoptera, Hydrophiloidea). Biologiske Skrifter, Det Kongeliege Danske Videnskabernes Selskab 40: 1\u2013368.", "Hofmann G., Flechtner G. 2003. Cercyon alpinus Vogt, 1968, im Fichtelgebirge (Coleoptera, Hydrophilidae). - Nachrichtenblatt der Bayerischen Entomologen 52(1/2): 20\u201323.", "Przewo\u017any M. 2004. Hydrophiloidea, In: Fauna Polski - charakterystyka i wykaz gatunk\u00f3w, Bogdanowicz B., Chudzick a E., Pilipiuk I., Skibinska E. (Eds.), MiIZ PAN, Warszawa 2004, pp. 149\u2013151; 156\u2013158.", "Przewo\u017any M. 2009. Hydrophilidae (Coleoptera) Polski \u2013 studium taksonomiczno-faunistyczne. Uniwersytet im. Adama Mickiewicza w Poznaniu, Wydzia\u0142 Biologii. Praca doktorska wykonana w Zak\u0142adzie Zoologii Systematycznej Instytutu Biologii \u015arodowiska (manuskrypt): 1\u2013313."]}